Microminipig, a Non-rodent Experimental Animal Optimized for Life Science Research: Novel Atherosclerosis Model Induced by High Fat and Cholesterol Diet - Hiroaki Kawaguchi; Noriaki Miyoshi; Naoki Miura; Makoto Fujiki; Masahisa Horiuchi; Yasukatsu Izumi; Hiroaki Miyajima; Ryoichi Nagata; Kazuhiro Misumi; Toru Takeuchi; Akihide Tanimoto; Hiroki Yoshida (Elsevier, 2011)
Atherosclerotic lesions were observed in male and ovariectomized female Microminipig (MMP) fed a high fat and cholesterol diet with sodium cholate (HFCD/SC) for 3 months. HFCD/SC induced hypercholesterolemia accompanied by an increase in serum total cholesterol (T-Cho), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and cholesterol ester (CE). Unlike the mouse or rabbit, a dominant LDL-C fraction in the intact MMP, similar to that in humans, was observed by serum lipoprotein analysis. HFCD/SC increased body weight gain. At the end of the experiment, computed tomography scans of conscious animals showed that HFCD/SC had decreased liver attenuation values (Hounsfield unit) and increased subcutaneous and abdominal fat, suggesting the induction of fatty liver and obesity. HFCD/SC induced atherosclerotic lesions in systemic arteries, including the external and internal iliac arteries, abdominal aorta, coronary artery, and cerebral arterial circle. Atherosclerosis and pathological findings induced by HFCD/SC in MMP were similar to those in humans. The MMP is a potentially suitable tool for investigating human atherosclerosis. Keywords:: atherosclerosis, cholesterol, diet, life-style, Microminipig